Exposure to NO2 in occupational built environments in urban centre in Lahore - Andleeb, S.; Ali, Z.; Afzal, F.; Razzaq, A. A.; Mehmood, T.; Noor, N.; Rasheed, F.; Nasir, Zaheer A.; Colbeck, Ian (Pakistan Agricultural Scientists Forum, 2015)
Increased economic growth, urbanisation and substantial rise in automobile vehicles has contributed towards the elevated levels of air pollution in major cities in Pakistan. Aone week study was conducted by using passive samplers to assess NO2 concentration in occupational built environments at two most congested and populated sites of Lahore. Both sites were locatedon the busy roads of Lahore. At Site-I the highest concentration was in outdoors followed by corridor and indoor. While at Site II all the sampling location wereindoors and level were comparable to that of outdoor levelsat Site I. The results suggest the likely contribution of ambient sources in exposure to indoor NO2 in educational and other occupational built environments in urban centres.